Multidimensional Tungsten Oxides for Efficient Solar Energy Conversion. Issue 2 (16th December 2021) - Zhang, Xing; Wei, Yanze; Yu, Ranbo
Abstract : Dimensionalities of materials have more profound connotations than barely the external morphologies. The mechanical, optical, electrical, and magnetic properties of a certain material can be significantly influenced by the spatial degrees of freedom of interactions/excitons. Herein, how multidimensionalities affect their physicochemical properties from the perspective of photoactive tungsten oxide (WO3 ) materials, which further influence their performances in solar energy conversion applications are looked at. Benefiting from the fruitful research efforts on WO3 ‐based photocatalysts and photoelectrodes, the key procedures in photoenergy conversion including light absorption, charge separation, and surface reaction, are discussed to elucidate the unique features, advantages, and challenges of the single‐dimensional WO3 heterostructures. Then the optoelectronic properties and performance of mixed‐dimensional WO3 heterostructures are investigated to show the synergistic effect between the specifically combined dimensionalities. The dynamic behaviors of excitons or charge carriers within the mixed‐dimensional structures and at their interfaces are inspected, with several photophysical or chemical phenomena noted for designing other photoactive metal oxide semiconductors. A bumper harvest of WO3 photovoltaics, photocatalysts, and photoelectrodes beyond dimensionality is on the way, hence, it is an opportune chance to evaluate the progress and foresee future directions in this fast‐moving research field. Abstract : Herein, the progress of multidimensional tungsten oxides (WO3 )‐based photoactive materials are introduced. To bypass the intrinsic limitations caused by spatial dimensionality and to enhance the optoelectronic properties for solar energy conversion, mixed‐dimensional WO3 materials are consequently summarized. The preliminary results in this fast‐growing field are anticipated to guide the development of diverse mixed‐dimensional photoactive materials.